2015
DOI: 10.1016/j.jdent.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of monolithic zirconia after dental adjustment treatments and in vitro wear simulation

Abstract: Careful polishing is recommended to keep surface roughness and phase transformation low.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 34 publications
3
77
0
14
Order By: Relevance
“…Though this will probably increase the chipping risk of the veneering porcelain, the use of monolithic TZP will solve the chipping problem, and the use of monolithic translucent TZP will also improve the appearance. In addition, smooth-polished TZP has been reported to cause less wear on the antagonist enamel, making it more clinically useful 24,34) . Furthermore, the fact that the flexural strength of all the monolithic TZP showed approximately 1,000 MPa indicate no requires for drastic increase in thickness compared with conventional crown restorations, and it may become a clinical benchmark for decreasing the amount of tooth to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Though this will probably increase the chipping risk of the veneering porcelain, the use of monolithic TZP will solve the chipping problem, and the use of monolithic translucent TZP will also improve the appearance. In addition, smooth-polished TZP has been reported to cause less wear on the antagonist enamel, making it more clinically useful 24,34) . Furthermore, the fact that the flexural strength of all the monolithic TZP showed approximately 1,000 MPa indicate no requires for drastic increase in thickness compared with conventional crown restorations, and it may become a clinical benchmark for decreasing the amount of tooth to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Preis et al [37] investigated the surface properties (roughness, composition and phase transformation) of monolithic zirconia after dental adjustment procedures (grinding and polishing) and wear simulation. The findings of the study revealed that grinding significantly increased the roughness of sintered zirconia, whereas, polishing significantly reduced R a .…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Intraoral adjustment thereby increased the zirconia surface roughness and, by implication, the wear damage. As a conclusion, a perfect polish has been claimed mandatory for a suitable wear resistance of zirconia and the opposing antagonists [5].…”
Section: Introductionmentioning
confidence: 97%